Torts - Davies, Martin; Malkin, Ian; Voon, Tania (Chatswood, NSW : LexisNexis, 2024)
"The tenth edition of Focus: Torts assists students to develop a better understanding of torts by identifying and explaining key areas of study. The authors use a straightforward, structured approach to help demystify even the most complex of legal concepts. Both common law principles and Australian statutory regimes are covered extensively, providing a detailed account of similarities and differences across all Australian jurisdictions. The text provides the reader with numerous opportunities to develop critical thinking skills by practising answers to hypothetical legal problems. The tenth edition incorporates recent case law, legislative changes and discussion questions intended to provoke reflection on the state of the law. Among other things, this new edition considers recent legislative changes introducing a serious harm threshold for defamation claims, as well as the following significant new cases: Binsaris v Northern Territory (HCA, 2020); Bird v DP (VSCA, 2023); Brocklands Pty Ltd v Tasmanian Networks Pty Ltd (TasSC, Full Ct, 2020); CCIG Investments Pty Ltd v Schokman (HCA, 2023); Comensoli v O'Connor (VSCA, 2023); Construction, Forestry, Maritime, Mining and Energy Union (CFMMEU) v Personnel Contracting Pty Ltd (HCA, 2022); Dean v Pope (NSWCA, 2022); East Metropolitan Health Service v Ellis (WASCA, 2020); Electricity Networks Corp v Herridge Parties (HCA, 2022); Ethicon Sàrl v Gill (FCA, Full Court, 2021); Fairfax Media Publications Pty Ltd v Voller (HCA, 2021); Google LLC v Defteros (HCA, 2022); Kozarov v Victoria (HCA, 2022); John XXIII College v SMA (ACTCA, 2022); Lewis v ACT (HCA, 2020); PCB v The Geelong College (VSC, 2021); Queensland Bulk Water Supply Authority (t/as Seqwater) v Rodriguez & Sons Pty Ltd (NSWCA, 2021); Roberts-Smith v Fairfax Media Publications Pty Ltd (No 41) (FCA 2023); Roy v O'Neill (HCA, 2020); Sydney Local Health District v Macquarie International Health Clinic Pty Ltd (NSWCA, 2020); Tapp v Australian Bushmen's Campdraft & Rodeo Association Ltd (HCA, 2022). Features: succinct and accessible discussion of key tort law principles; user-friendly design and strong pedagogic features; comprehensive coverage of all Australian jurisdictions; timesaving online support for lecturers."--Publisher's website.
Includes bibliographical references and index.
Mode of access : Available online.
Keywords: Libel and slander; Negligence -- Australia; Reasonable care (Law) -- Australia; Torts -- Australia; Trespass; Law; Electronic books